High-frequency properties and electromagnetic wave attenuation for hexaferrite composites - Kong, Ling Bing (2014)
Static, high-frequency magnetic properties and EM attenuation characteristics have been studied for Ti substituted Z-type hexaferrites, Ba3Co2Fe24-xTixO41 with x=0-0.6, and ferrite/silicone composites. The results show that Ti substitution is able to enhance μ’ and μ” and improve EM attenuation with expanded relative bandwidth WR and decreased thickness of composites. The Ba3Co2Fe24-xTixO41 composite with x=0.3 has best EM attenuation properties with low reflectivity and broad bandwidth at C and X bands (4-12 GHz). WR of 3.7 for R<-10 dB and thickness of only 0.30 cm are achieved.